Secreted and surface proteome and transcriptome of Opisthorchis felineus - Wong, Yide; Pearson, Mark S.; Fedorova, Olga; Ivanov, Vladimir; Khmelevskaya, Ekaterina; Tedla, Bemnet; Arachchige, Buddhika Jayakody; Reed, Sarah; Field, Matt; Laha, Thewarach; Loukas, Alex; Sotillo, Javier (Frontiers in Parasitology, 2023)
Introduction Opisthorchis felineus, Opisthorchis viverrini, and Clonorchis sinensis are the most medically important species of fish-borne zoonotic trematodes. O. felineus is endemic to the river plains of Western Siberia and Eastern Europe, and it is estimated that more than 1.6 million people could be infected with this parasite. Chronic opisthorchiasis may lead to significant gastrointestinal and hepatobiliary pathology. This study aimed to identify and characterize proteins from the secreted and tegumental proteomes of O. felineus. Methods Adult flukes were collected from experimentally infected hamsters and cultured in vitro in serum-free media. We extracted proteins from different compartments of the O. felineus secretome, including (i) soluble excretory/secretory (ES) products; (ii) secreted 15K-extracellular vesicles (EVs); and (iii) tegument. Results We also generated a transcriptome using long-read sequencing, and when this was combined with high-resolution mass spectrometry, sodium dodecyl sulfate–polyacrylamide gel electrophoresis (SDS-PAGE) separation, and protein digestion, we identified 686, 894, 389, 324, and 165 proteins from the ES, 15K-EV, and the three sequentially extracted tegument (TEG) protein fractions, respectively. We conducted in-depth gene ontology and protein family analyses on the identified proteins and discussed comparisons against similar proteome data sets acquired for the Southeast Asian liver fluke O. viverrini and the Chinese liver fluke C. sinensis. Discussion The information from this study will form a biologically relevant data set of O. felineus proteins that could be used to develop diagnostic and therapeutic tools to manage the human cost of O. felineus infection and its associated comorbidities.